Perencanaan Enterpreneurship Bagi Calon Pekerja Migran Indonesia Pasca Kepulangan Di LPK Wisma Berkah Sejahtera - Umi Handayani; Hendrike Priventa; Rosalina Wahyu Riani; Kustiyono; Izza Aulia; Adilla Wira Wati (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The number of Indonesian migrant workers departing from Japan has increased since the COVID-19 pandemic ended. This increase not only benefits the Indonesian people but also presents challenges when Indonesian migrant workers in Japan are repatriated. The main problem is the lack of entrepreneurial competency acquired by repatriated Indonesian migrant workers, which has an impact on unemployment. Therefore, in response to this phenomenon, the Community Service Team held outreach and entrepreneurship training activities for prospective Indonesian migrant workers in Japan to help them develop entrepreneurial planning competencies. The focus of these activities was on obstacles and barriers, financial literacy, and business planning. The results of these activities showed that 80% of participants had ideas for entrepreneurship after returning to Indonesia.